Papillary thyroid carcinoma in a 15-year-oldfemale adolescent - Jorge Luis Soriano-Lorenzo; Omar Miguel Pérez-Perdomo; Karla Zaldivar-Blanco (Universidad Médica Pinareña, 2020)
Introduction: tumors of the thyroid gland in pediatric ages have an incidence between 1,5 % and 3,4 %.